A patient's dilemma : to litigate or otherwise - Ravichandran, N.; Radha, R., active 2018 (London : Indian Institute of Management, Ahmedabad, 2018)
The patient, a middle-aged woman was advised hysterectomy by an Oncology Gynaecology surgeon, based on the patient's health conditions, symptoms and clinical investigations. The patient however, decided to seek out a gynecologist for a second opinion on whether she should get a hysterectomy. The second consultation was far from a pleasant experience and it appeared as though the consultant was a leveraging an opportunity to maximize revenue. Students are asked to consider if legal action against the consultant gynecology would be fruitful in this instance.
Originally Published In Ravichandran, N., & Radha, R. (2018). A Patient's Dilemma: To litigate or otherwise. QM0283. Ahmedabad, India: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Gynecologists -- Malpractice -- Case studies; Gynecology -- Law and legislation -- Case studies